Changes of serum uric acid level during acute gout flare and related factors - Zhang, Jie; Sun, Wenyan; Gao, Fei; Lu, Jie; Li, Kelei; Xu, Yijun; Li, Yushuang; Li, Changgui; Chen, Ying (Frontiers in Endocrinology, 2023)
Objective: By studying the changes of serum uric acid (SUA) in acute stage and remission stage of gouty arthritis, we aimed to explore the relationship between the changes of SUA level and free glucocorticoids and inflammatory factors. Methods: A prospective, longitudinal study was conducted on 50 acute gout patients in the dedicated gout clinic of the Affiliated Hospital of Qingdao University. Blood and 24-hour urine samples were collected during the acute phase and two weeks after the initial visit. Patients with acute gouty arthritis were treated primarily with colchicine and nonsteroidal anti-inflammatory drugs. Results: A total of 32 patients completed the two-week follow-up trial. SUA levels were significantly downregulated during the acute flare than after the flare (464.14 ± 90.97 vs. 527.36 ± 86.90 μmol/L, p < 0.001). The 24-hour fractional excretion of uric acid (24 h FEur) (5.54 ± 2.82% vs. 4.68 ± 2.83%, p < 0.001) and 24-hour urinary uric acid excretion (24 h Uur) (663.08 ± 249.48 μmol/L vs. 540.87 ± 263.18 μmol/L, p = 0.001) increased significantly in patients during the acute phase. The percent change in SUA was associated with those in 24 h FEur and C-reactive protein. Meanwhile, the percent change in 24 h Uur was associated with those in 24-hour urinary free cortisol, percent change in interleukin 1β and interleukin 6. Conclusion: Decreased SUA level during the acute gout flare was associated with increased excretion of urinary uric acid. Inflammatory factors and bioactive free glucocorticoids may play significant roles in this process.